Temporal change in the composition of the bird community in isolated forests in Kuala Lumpur, Malaysia - Ramli, Rosli (Malaysian Journal of Science, 2001)
The effects of forest disturbance on birds inhabiting three urban forest islands around Kuala Lumpur, Malaysia, were studied. This study was done on forest islands located in city areas, i.e., i Bukit Gasing Forest Reserve (BGF), Taman Seputih Forest (TSF) and the patch of green area in University of Malaya campus (UMF). The forest fragments have different sizes; BGF is the largest (45 ha) followed by TSF (7 ha) and UMF (0.5 ha). Study was carried out in 1991 and 1997 to examine the effects of forest disturbance on the composition of bird community inhabiting each study area. Direct observation method had recorded more birds compared to mist-netting. Results has shown that there is no changes in species composition of birds inhabiting TSF, contrary to bird community in UMF and BGF, that shows major changes. Four species had totally vanished from BGF and 10 species of UMF had suffered local extinction. The main factor for this reduction is habitat degradation and/or habitat loss around and within the study areas due to rapid urbanization. ln addition to this, direct human disturbance such as poaching also plays as a contributing factor.